THE INFLUENCE OF BUDGETING PARTICIPATION AND ASYMMETRIC INFORMATION AGAINST THE BUDGETING VARIANTS REFERS TO THE ORGANIZATION COMMITMENT AS THE INTERVENING VARIABLE OF THE SURVEY AT FOOD AND BEVERAGE COMPANY IN THE INDUSTRIAL AREA JABABEKA KARAWANG - Syarief Gerald Prasetya; Yustiana Wardhani (The Accounting Journal of Binaniaga, 2016)
The study was based on the issue of managers in setting budgets often the difference (variance) is quite large and aims to demonstrate empirically the direct and indirect effects of budgetary participation and information asymmetry partially on budgetary slack. The analytical method used is path analysis with the participation of the budget, the asymmetry of information and organizational commitment as exogenous and endogenous budgetary slack variables. The sample used in this study as many as 78 people functional managers who have a tenure of more than five years, so hopefully they have experience in budgeting.The survey results revealed that the budgetary participation has positive effect directly against budgetary slack, the information asymmetry positive effect directly against budgetary slack, budgetary participation negatively impact directly on organizational commitment, the information asymmetry negative effect directly on organizational commitment, organizational commitment negatively affect directly to the budgetary slack, budgetary participation indirect positive effect on budgetary slack through organizational commitment, the information asymmetry indirect positive effect on budgetary slack through organizational commitment and it is known that the model in the study track is fit.Keywords: budgetary participation, information asymmetry, organizational commitment and budgetary gap.